Association between ketosis and metabolic adaptation at the level of resting metabolic rate. Issue 8 (August 2021) - Martins, Catia; Roekenes, Jessica; Hunter, Gary R.; Gower, Barbara A.
Summary: Background: The ketone body β-hydroxybutyrate (βHB) has been shown to act as a signaling molecule that regulates metabolism and energy homeostasis during starvation in animal models. A potential association between βHB and metabolic adaptation (a reduction in energy expenditure below predicted levels) in humans has never been explored. Objective: To determine if metabolic adaptation at the level of resting metabolic rate (RMR) was associated with the magnitude of ketosis induced by a very-low energy diet (VLED). A secondary aim was to investigate if the association was modulated by sex. Methods: Sixty-four individuals with obesity (BMI: 34.5 ± 3.4 kg/m 2 ; age: 45.7 ± 8.0 years; 31 males) enrolled in a 1000 kcal/day diet for 8 weeks. Body weight/composition, RMR and βHB (as a measure of ketosis) were determined at baseline and week 9 (W9). Metabolic adaptation was defined as a significantly lower measured versus predicted RMR (from own regression model). Results: Participants lost on average 14.0 ± 3.9 kg and were ketotic (βHB: 0.76 ± 0.51 mM) at W9. A significant metabolic adaptation was seen (−84 ± 106 kcal/day, P < 0.001), with no significant differences between sexes. [βHB] was positively correlated with the magnitude of metabolic adaptation in females (r = 0.432, P = 0.012, n = 33), but not in males (r = 0.089, P = 0.634, n = 31). Conclusion: In females with obesity, but not males, the larger the [βHB] under VLED, the greater the metabolic adaptation at the level of RMR. More studies are needed to confirm these findings and to explore the mechanisms behind the sex difference in the association between ketosis and metabolic adaptation. Trial registration name: Clinicaltrials.gov. Study registration ID: NCT02944253. URL: https://clinicaltrials.gov/ct2/show/NCT02944253 .